2000
DOI: 10.1074/jbc.c000600200
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 11β-Hydroxysteroid Dehydrogenase Mediates Glucocorticoid Activation and Insulin Release in Pancreatic Islets

Abstract: Metabolic transformation of glucocorticoid hormones constitutes a determinant of their cell-specific effects.The most important reaction for this class of steroids is the reversible C11 keto/␤-hydroxyl conversion between receptor-binding 11␤-OH steroids and the nonbinding 11-oxo compounds, carried out by 11␤-hydroxysteroid dehydrogenases (11␤-HSDs). In this study, we determined the role of glucocorticoid conversion by 11␤-HSD in pancreatic islets and its function in the regulation of insulin release. Pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
91
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 35 publications
9
91
2
1
Order By: Relevance
“…11 -HSD1 is expressed in pancreatic islets and its expression is higher in islets from obese rodents where inhibition with carbenoxolone or selective 11 -HSD1 inhibitors (Davani et al, 2000, Ortsater et al, 2005 alleviates the 11-M a n u s c r i p t 14 ketoglucocorticoid-mediated suppression of insulin secretion in these models. An intriguing new finding suggests that 11 -HSD1 is expressed most highly in the glucagon secreting alpha cells, where the authors suggested the effects on insulin secretion might occur through a paracrine modulation of insulin secretion by this hormone (Swali et al, 2008).…”
Section: Other Important Sites Of 11 -Hsd1 Expressionmentioning
confidence: 99%
“…11 -HSD1 is expressed in pancreatic islets and its expression is higher in islets from obese rodents where inhibition with carbenoxolone or selective 11 -HSD1 inhibitors (Davani et al, 2000, Ortsater et al, 2005 alleviates the 11-M a n u s c r i p t 14 ketoglucocorticoid-mediated suppression of insulin secretion in these models. An intriguing new finding suggests that 11 -HSD1 is expressed most highly in the glucagon secreting alpha cells, where the authors suggested the effects on insulin secretion might occur through a paracrine modulation of insulin secretion by this hormone (Swali et al, 2008).…”
Section: Other Important Sites Of 11 -Hsd1 Expressionmentioning
confidence: 99%
“…While enzyme activity and cellular localisation studies have not been performed, incubation with 11-dehydrocorticosterone decreased glucose-stimulated insulin secretion (GSIS) in a dose-dependent manner. This was reversed by incubation with 11β-HSD1 inhibitors carbenoxolone [4,6] and BVT.2733 [6], and partially reversed by GR antagonist RU38486 [6].…”
mentioning
confidence: 95%
“…11β-HSD1 is present at high levels in liver, adipose tissue and muscle, but it has also been reported to be present in pancreatic islets [4]. The activity of 11β-HSD1 primarily generates active glucocorticoid and cortisol (corticosterone in rodents) from inactive cortisone (11-dehydrocorticosterone in rodents) via its oxo-reductase activity [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In rodents, fetal exposure to glucocorticoids induces IUGR at birth, and impaired glucose tolerance [13][14][15] and hypertension [16,17] at adult age. Numerous studies have investigated the deleterious effects of glucocorticoids on pancreatic beta cell function, showing altered glucosestimulated insulin release, both in vitro in islets treated with dexamethasone [18][19][20] and in vivo in mice overexpressing GR in the beta cells [21,22].…”
Section: Introductionmentioning
confidence: 99%